Performance Anxiety: Audit Culture and the Neoliberal New Zealand University - Stahl, Geoff (Culture Unbound, 2015)
This essay considers the role of audit culture and research output measurement regimes in Aotearoa/New Zealand. It explores the nature of neoliberalism and how it has worked its way into research and publishing, as well as departmental and teaching, contexts. This forms an important part of what Alison Hearn has called the promotional university, complete with bibliometrics and the attendant disciplinary mechanisms that work to produce “productive” researchers.